The Effect Of Employing The Strategy Of The Talkative Groups On The Achievement And Attitudes Of Chemistry For Fifth Grade Students Applied Science - Abbas Mohammed, Anwar (Opción, 2019)
The study aimed to reveal the impact of employing the strategy of the talk- ative groups on the achievement and academic tendencies of chemistry for students of the fifth grade of applied science for the academic year (2018 - 2019), and to achieve this goal the researcher used the experimental method on the sample of the study consisting of (50) students, prepared achievement test falls Under (60) paragraphs, and the scale of tendencies for chemistry falls under (30) paragraphs, and after the researcher completed the research experiment according to what was planned: The superiority of the experimental group studied according to the strate- gy of the talkative groups was found in the post-application of the test of achievement and attitudes of chemistry.